Application of 1D Shallow Flow Model for Simulation of Pollution Fate and Streamflow - Nor Azlina, Alias; Lariyah, Mohd Sidek (Springer, 2016)
Numerical models especially two-dimensional (2D) models have long been used in simulating hydrodynamics and its associated processes such as sediment transport, pollutant dispersion, and flooding are caused by overtopping or breaching of river banks. However, due to the complexity of the river geometries, it is still difficult to resolve the problematic river in a 2D manner. Thus, a one-dimensional (1D) component model is needed to analyze complex flow hydrodynamics under flood conditions. As solute transport also greatly impacts the local environment and is closely related to the water quality in shallow water bodies, the prediction of pollutant fate is also included in this paper. Thus, this paper focuses on developing a numerical model to simulate shallow flow hydrodynamics in the context of irregular profiled open channels to predict depth-averaged water level and pollutant transport. The scope of work is limited to the development of a 1D model and verification of the model against benchmark tests and laboratory measurements. Presented in this paper is the development of an integrated model with fully dynamic shallow water equations (SWE’s) and the advection–diffusion equation. Results demonstrated are the comparisons between the numerical results and data obtained through experimental procedures or from published analytical solutions in terms of flow depth and solute concentration. Closed agreement is achieved for all tests, and the model was therefore applied in Sungai Penchala, Malaysia.